Computed tomography for determining liver iron content in primary haemochromatosis. - Chapman, R W (1980)
Dual-energy computed tomography (CT) was used to estimate hepatic iron concentration in eight patients with primary haemochromatosis with varying degrees of iron overload. The values corresponded closely with these derived from chemical analysis of liver tissue obtained by biopsy (correlation coefficient 0.993). Dual-energy CT therefore seems to provide an accurate and non-invasive alternative to liver biopsy as a means of measuring liver iron concentration in patients with primary haemochromatosis and possibly other iron overload states.